(Intermediate Moisture Foods) - Wuri Handono, S (Balai Besar Industri Agro, 1990)
The science and technology of intermediate moisture foods has advanced during the last 30 e. Knowledge of the relationship of water activity and the formulation as well as the stability of intermediate moisture food products has advanced considerably during this period. In this article, intermediate moisture foods are reviewed with respect to their definition, principles technology, relationship with Aw and general stability.